2023
DOI: 10.1063/5.0140317
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nonlinear water wave interaction solutions and energy exchange between different wave modes

Abstract: In this study, we consider the ideal fluid model of an inviscid fluid, assuming that the fluid motion is adiabatic; the flow is irrotational, that is, the individual fluid particles do not rotate; vorticity ω̃=0; and the flow is incompressible, in which the density of fluid particles does not vary significantly with fluid motion and can be considered constant throughout the fluid volume and throughout the motion. We start with equations representing continuity, conservation of momentum, conservation of entropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…By using equation (46) and the Adomian polynomials for nonlinear term as given in equation (25). Hence, solution…”
Section: Anatomy Of the Ff-kdv Equation Using Ytdmmentioning
confidence: 99%
See 1 more Smart Citation
“…By using equation (46) and the Adomian polynomials for nonlinear term as given in equation (25). Hence, solution…”
Section: Anatomy Of the Ff-kdv Equation Using Ytdmmentioning
confidence: 99%
“…One of the PDEs that describes a broad spectrum of physical nonlinear phenomena as well as engineering materials is the well-known Korteweg-de Vries (KdV) equation [21][22][23][24][25][26]. This equation and its family, whether it contains third-order dispersion [27][28][29] or fifth-order dispersion [30][31][32] or other physical effects such as collision and viscosity forces, have effectively elucidated numerous nonlinear structures that emerge and propagate in diverse physical and engineering systems, including fluid physics and plasma physics.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the wave-packet behaviours of both equations cannot be fully determined via the analytical methods, except with certain initial and boundary conditions [3,4,[7][8][9][10][11][12]. Therefore, various conventional meshbased numerical methods have been introduced to explore the Boussinesq and Camassa-Holm equations, such as the finite-element method, the finite volume method and the spectral method [20][21][22][23][24][25][26][27]. It has been revealed that for the Boussinesq equation in the 'good' case, those numerical methods can provide satisfactory results, while for the Boussinesq equation in the 'bad' case, most numerical methods fail due to the instability of the equation, even for the simulation of the simplest bell-shaped solitons [20,21].…”
Section: Introductionmentioning
confidence: 99%